Resource funds: Stabilising, parking, and inter-generational transfer - Venables, AJ; Wills, SE (Oxford University Press, 2016)
The paper explores strategies for managing revenue from natural resources, focusing on the balance between domestic and foreign asset accumulation. It suggests that domestic asset accumulation is the priority in developing countries, while there are three motives for accumulating foreign assets; inter-generational transfer, temporary ‘parking’ of funds, and stabilisation. The paper argues that the first of these is inappropriate for low income countries. The second is required if it is difficult to absorb extra spending in the domestic economy and takes time to build up domestic investment. The third is important, and depends on the extent to which the economy has other ways of adjusting to shocks.